Interoperability and portability of cloud service enablers in a PaaS environment - Cunha, David (2012)
Nowadays, the competition in the telecommunications market is exciting and new entities with value-added services have emerged over the core network of Telecommunications operators (Telcos). These new participants have taken out the operators’ relevance since they are entirely agnostic from infrastructure service connectivity. Therefore Telcos, like Portugal Telecom Inovação (PTIN), need to focus on the provision of services to a user’s point of view to not become just a dumb-pipe between the consumers and Cloud service providers. This paper proposes a definition of a distributed architecture that allows developers to create and expose services through a Service Delivery Platform (SDP). The benefit of such Cloud-enabled SDP architecture is the portability of service enablers between Platform-as-a-Service (PaaS) providers through a standardized API. Service developers may thus select the more suitable PaaS offering in order to build on-top applications, based on the performance required by a service. An example of applications which can take advantage from more versatile Cloud platforms, is the delivery of mobile context-aware services that react to both environment and user conditions selecting the right type of content (e.g. photos, videos, etc.) to deliver.